2007
DOI: 10.1007/s10286-007-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in short-term measures of heart rate variability after eight weeks of cardiac rehabilitation

Abstract: This is the first study to show significant increases in raw LF and HF power derived from short-term ECG recordings in CR patients. These measures are risk factors for future cardiac event. As CR is associated with increases in these measures it may be viewed as an effective therapy capable of bringing about favourable alterations in autonomic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…Our results are confirmed by that of Jurca et al in 2004 who, after 8 weeks of moderate exercise training in females, showed improved vagal modulation of heart rate on 10-min resting ECGs [36]. Many previous studies done on diseased populations to evaluate the effect of short-term exercise intervention on short-term HRV modification assessed only supine variables [37][38][39][40][41][42][43]. Sandercock et al in 2007 observed significant increases in the supine RR interval, SDRR, LF(ln) and HF In the present study, only the RR interval increased significantly in the supine position, while the other variables did not show significant changes in favour of the exercise group.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are confirmed by that of Jurca et al in 2004 who, after 8 weeks of moderate exercise training in females, showed improved vagal modulation of heart rate on 10-min resting ECGs [36]. Many previous studies done on diseased populations to evaluate the effect of short-term exercise intervention on short-term HRV modification assessed only supine variables [37][38][39][40][41][42][43]. Sandercock et al in 2007 observed significant increases in the supine RR interval, SDRR, LF(ln) and HF In the present study, only the RR interval increased significantly in the supine position, while the other variables did not show significant changes in favour of the exercise group.…”
Section: Discussionsupporting
confidence: 90%
“…This shift toward greater vagal modulation may positively affect the prognosis of individuals with a variety of morbidities (53). (57) found that following an eight-week cardiac rehabilitation program, 21 male and 17 female participants had significant increases in HRV parameters compared with those not participating in the training program. In another study (58), researchers reported a 25% increase in SDNN, a 69% increase in the square root of the mean of the sum of squares of successive N-N interval differences, a 120% increase in the number of successive N-N intervals differing by more than 50 ms divided by the total number of successive N-N intervals and a 30% reduction in LF/HF ratio after 22 MI patients completed an eight-week endurance rehabilitation program.…”
Section: Exercise Therapy and Hrv Modification In Clinical Populationsmentioning
confidence: 99%
“…The outcomes of these tests provide important information regarding exercise capacity and effectiveness of rehabilitation treatments [4]. They are used in exercise prescription and risk stratification [5].…”
Section: Introductionmentioning
confidence: 99%